2020
DOI: 10.13106/jafeb.2020.vol7.no10.1129
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Usage of University Mobile Application Among University Students

Abstract: This study investigates the factors influencing the usage of PSAU Mobile Application by the students at Prince Sattam bin Abdulaziz University (PSAU). This study used Technology Acceptance Model (TAM) as a framework to predict the factors influencing 67 students' usage of PSAU M-Application. The results of this study were consistent with the TAM framework in predicting the actual usage of the PSAU mobile application for academic activities. The results indicated a significantly positive association of the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
1
9
0
3
Order By: Relevance
“…The last point to make about H10 is that there is empirical data to support it, which shows that having a positive behavioral intention may lead to the use of an e-wallet to pay zakat during the pandemic where it is consistent with the findings of the research by Febrianto et al (2018) and Rattanaburi & Vongurai (2021). In the current study, behavioral intention was shown to have a favorable and substantial impact on the actual use of e-wallet apps for zakat payment, both favorably and significantly.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The last point to make about H10 is that there is empirical data to support it, which shows that having a positive behavioral intention may lead to the use of an e-wallet to pay zakat during the pandemic where it is consistent with the findings of the research by Febrianto et al (2018) and Rattanaburi & Vongurai (2021). In the current study, behavioral intention was shown to have a favorable and substantial impact on the actual use of e-wallet apps for zakat payment, both favorably and significantly.…”
Section: Discussionsupporting
confidence: 75%
“…It was confirmed byGerpott & Thomas (2014) that intention was the most significant predictor of technology adoption. According toJaradat & Faqih (2014), Febrianto et al (2018, andRattanaburi & Vongurai (2021), behavioral intention influences the use of technological advancements. Therefore, the fundamental purpose of this study is to better understand the link between behavior intention and actual use of e-wallet services in zakat payment during the pandemic.…”
mentioning
confidence: 99%
“…Proses pengembangan aplikasi akan dilakukan dengan bahasa pemrograman Swift dan menggunakan Challenge Based Learning seperti pada penelitian Fojtik (2020) dan Li & Yang (2019). Setelah pengembangan aplikasi selesai dilakukan, penulis melakukan analisis keefektifannya dengan menggunakan model TAM (Technology Acceptance Model) sebagai model penelitian (Aljaaidi, Bagais, & Sharma, 2020).…”
Section: Pendahuluanunclassified
“…Pada studi kuantitatif dalam menganalisis efektivitas penggunaan aplikasi, penulis menggunakan Technology Acceptance Model (TAM) sebagai model yang diadopsi dari penelitian Aljaaidi, Bagais, & Sharma (2020). Penelitian tersebut memiliki variabel penelitian yang meliputi Perceived Ease of Use, Perceived Usefulness, Attitude towards using, Behavioural Intention to Use dan Actual Use.…”
Section: Model Penelitianunclassified
See 1 more Smart Citation